Anti-aesthetic and its formal representations in contemporary industrial product design (Journal of the College of Basic Education, 2025)
This study examines anti-aesthetics in contemporary industrial design, critiquing traditional notions of harmony, proportion, and beauty. Influenced by movements such as Dadaism, Surrealism, and Brutalism, anti-aesthetic design emphasizes rawness, imperfection, and functionality, disrupting conventional ideas of beauty and usability through unconventional materials and forms. Using case studies of iconic designs like Philippe Starck’s Juicy Salif, Marijn van der Poll’s Do Hit Chair, and Jurgen Bey’s Tree Trunk Bench, the research identifies strategies such as raw material use, extreme functionality, and rejection of polished aesthetics.Findings reveal that anti-aesthetic design is a purposeful approach to provoke thought, foster critical engagement, and redefine relationships between form, function, and materiality, ultimately challenging traditional and consumer-driven design norms.